2003
DOI: 10.1023/b:appa.0000005108.72167.74
|View full text |Cite
|
Sign up to set email alerts
|

Propensity towards cannibalism amongHypoaspis aculeiferandH. miles, two soil-dwelling predatory mite species

Abstract: In biological control programmes, the two predatory soil mites Hypoaspis aculeifer and H. miles are often applied against soil-borne pests like mushroom flies, springtails and mites. Although the mites show high consumption rates on varying prey types in Petri dish experiments and in greenhouses, their overall efficiency is sometimes limited. We hypothesized that intraspecific interactions, like cannibalism, could contribute to this decreased competence. Therefore, experiments were conducted to show the propen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 3 publications
1
25
0
Order By: Relevance
“…It appears likely that all commercial cultures available under the name of H. miles are actually S. scimitus. What is less clear is the identity of mites identified as H. miles in earlier studies (Schereef et al 1980;Hoda et al 1986;Rasmy et al 1987) and from studies that do not clearly identify the source of the mites used Ali et al , 1999Berndt et al 2003).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It appears likely that all commercial cultures available under the name of H. miles are actually S. scimitus. What is less clear is the identity of mites identified as H. miles in earlier studies (Schereef et al 1980;Hoda et al 1986;Rasmy et al 1987) and from studies that do not clearly identify the source of the mites used Ali et al , 1999Berndt et al 2003).…”
Section: Discussionmentioning
confidence: 97%
“…For example, a number of papers have been published on Stratiolaelaps (=Hypoaspis) miles (Berlese), and on the related laelapid Geolaelaps (=Hypoaspis) aculeifer (Canestrini), most notably on their biology and ecology (Schereef et al 1980;Hoda et al 1986;Rasmy et al 1987;Enkegaard et al 1997;Ydergaard et al 1997;Berndt et al 2003) and on their potential use for managing pests in greenhouses (Gillespie and Quiring 1990;Chambers et al 1993;Brødsgaard et al 1996), mushroom production facilities (Ali et al , 1999Jess and Kilpatrick 2000), and in the field (Lesna et al 1995;Rat-Morris 1999). Stratiolaelaps miles is widely marketed in North America as a biological control agent to manage dark-winged fungus gnats, Bradysia spp.…”
Section: Introductionmentioning
confidence: 99%
“…One exception was for M. insignitus, where larvae were not replaced daily for a period of 2 days due to a lack of experimental organisms. Immature mites were removed from arenas immediately after detection to prevent cannibalism, although cannibalism is rare for G. aculeifer and S. miles (Berndt et al 2003). Experiments were maintained for 7-14 days, depending on the mite species (Table 2).…”
Section: Predation Experimentsmentioning
confidence: 99%
“…The cannibalistic behavior observed in H. aculeifer might also had contributed to their decrease (Berndt et al 2003), but this should have been limited since this is only observed if no alternative prey is available (Usher and Davis 1983).…”
Section: Intrinsic Changes In the Microcosm Communitymentioning
confidence: 99%